COMPARISON OF INTRAVENOUS TIROBAN AND INTRACORONARY TIRO BAN IN TERMS OF ADVERSE CARDIAC EVENTS AND CEREBROVASCULAR ACCIDENTS - AMTAL, T; KHAN, SA; BIBI, B; ASHRAF, J; RAHMAN, M; NAQVI, KA (Biological and Clinical Sciences Research Journal, 2024)
Patients with acute coronary syndrome (ACS) and a high thrombus burden undergoing percutaneous coronary intervention (PCI) are at risk for major adverse cardiac events (MACE) and cerebrovascular complications. Tirofiban, a glycoprotein IIb/IIIa inhibitor, is used to reduce thrombus burden, with administration routes (intracoronary vs. intravenous) potentially influencing outcomes. Limited data exist comparing the effects of intracoronary and intravenous administration of tirofiban on adverse cardiac and cerebrovascular events in these high-risk patients Objective: To compare intravenous tiroban and intracoronary tiroban in terms of adverse cardiac events and cerebrovascular accidents. Methods: A randomized controlled trial was conducted on eighty patients aged ≥ 40 years with ACS and high thrombus burden scheduled for PCI were randomized, with 40 patients receiving intracoronary tirofiban (Group A) and 40 receiving intravenous tirofiban (Group B). Group A received a bolus of tirofiban (10 µg/kg) directly at the thrombus site during PCI, followed by a 24-hour intravenous infusion (0.15 µg/kg/min). Group B received the same bolus dose intravenously, followed by an identical infusion protocol. MACE and cerebrovascular accidents were compared in both groups. Results: MI occurred in 5 patients (12.5%) in Group A while 6 patients (15.0%) in Group B (p=0.74). Repeat revascularization was required in 8 patients (20.0%) in Group A and 5 patients (12.5%) in Group B (p=0.36). Cerebrovascular events occurred in 4 patients (10.0%) in Group A and 7 patients (17.5%) in Group B (p=0.33). Conclusion: Both intracoronary and intravenous tirofiban administration result in comparable outcomes regarding MACE and cerebrovascular events in patients undergoing PCI with a high thrombus burden.